STUDI PIROLISIS AMPAS TEBU DENGAN MENGGUNAKAN INSTRUMEN PYROLYSIS-GAS CHROMATOGRAPHY-MASS SPECTROMETRY (Py-GC/MS) - Nana Lestari; RR Dirgarini Julia Nurlianti Subagyono; Veliyana Londong Allo (PROSIDING SEMINAR KIMIA, 2022)
A pyrolysis study of a bagasse using a pyrolysis-gas chromatography-mass spectrometry (Py-GC/MS) instrument was carried out. This research was conducted to determine the chemical and physical characteristics of bagasse and to determine the chemical composition of the pyrolysis products of bagasse. Pyrolysis of biomass were carried out at three temperatures, namely 350°C, 450°C and 550°C. Bagasse had a moisture content of 12 ± 0.004%, ash content 2.43 ± 0.001%, cellulose content 58%, lignin content 11 ± 0.02% and 10% hemicellulose content. Based on the percent product area in the pyrogram, bagasse pyrolysis products contained lignin derivative products (16-23%) and cellulose/hemicellulose derivative products 61-66%. Keywords: Pyrolysis, Py-GC/MS, Bagasse